Analisis Kontribusi Industri Pengolahan Terhadap Produk Domestik Regional Bruto Di Kabupaten Jayapura - Tanudy, Ayub; Syafii, Muhamad (Rifa'Institute, 2021)
The purpose of the study was to determine the contribution of the manufacturing sector to the gross regional domestic product in Jayapura district. This method uses qualitative analysis, namely analyzing data in the form of descriptions that are relevant to the problem raised. Where this analytical tool will be used to describe the factors that affect the acceptance of the value of the regional gross domestic product of Jayapura Regency. The calculation results show that the manufacturing sector in 2016 contributed to the formation of the value of the gross regional domestic product by 4.98 percent while the remaining 95.02 percent. The results of the calculation of the contribution of the construction sector in 2017 decreased in percentage compared to 2016 of 0.7 percent. The results of the calculation of the contribution of the manufacturing sector in 2018 decreased in percentage but not at the nominal value, which was 4.79 percent. The results of the calculation of the contribution of the processing industry sector in 2019 increasingly showed a negative trend in percentage terms but the nominal value experienced a good increase where it increased by 4.49 percent or decreased by 0.30 percent from the previous year and still shows a positive trend. The results of the calculation of the contribution of the manufacturing industry sector in 2020 increasingly show a positive trend both in percentage and nominal value where the increase is 4.77 percent